Methane and nitrous oxide dissolved gas concentrations from rivers in the North American Arctic (2017–2019) - Cara C M Manning; Zhiyin Zheng; Lindsay Fenwick; Ross D McCulloch; Ellen Damm; Robert W Izett; William J Williams; Sarah Zimmermann; Svein Vagle; Philippe Daniel Tortell (PANGAEA, 2022)
This dataset contains methane and nitrous oxide dissolved gas concentration and dissolved methane carbon isotope data from rivers in the Canadian Arctic Archipelago region collected between 2017-2019. River samples were collected during CCGS Amundsen cruises using a helicopter to travel to the rivers. At each river site, river water was pumped through tubing using a peristaltic pump. Water was collected into glass serum bottles and allowed to overflow three times before preserving with mercuric chloride and sealing with butyl rubber stoppers and aluminum crimp seals. Gas concentrations were determined using a purge and trap system coupled to a gas chromatograph/mass spectrometer, following the method of Capelle et al. (2015). For methane δ13C, samples (one sample per event) were pre-concentrated through a purge and trap system (Finnigan PreCon Trace Gas Pre-Concentrator) and measured with a Finnigan Delta XP Plus mass spectrometer following the method of Damm et al. (2015).
In: Manning, CCM et al. (2022): Methane and nitrous oxide dissolved gas concentrations and sea-air fluxes from rivers and seawater in the North American Arctic (2015–2019) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.941201